Ethics beyond leadership: can ethics survive bad leadership?. Issue 3 (10th July 2020) - Roque, Ana; Moreira, José Manuel; Dias Figueiredo, José; Albuquerque, Rosana; Gonçalves, Helena
Abstract : Purpose: The purpose of this paper is to contribute to the relaxion on what can be done to develop ethical cultures that may be less permeable and more resilient to changes in leadership from an ethical point of view. The influence of leaders on organisational ethics is recognised, and there are even those who consider that it is not possible to maintain an ethical culture when leaders are not engaged. But, if this theory is true, all business ethics programmes that can be created, and the cultures that can gradually be developed in organisations, will always have their existence and robustness suspended at each leadership change. How to maintain an ethical culture beyond leadership? Design/methodology/approach: As a strategy, we used the case study with a narrative methodology, in which a chief executive officer (CEO) and a chief compliance officer (CCO) narrate in the first person a case of perceived collapse of the ethical culture of a multinational company. Findings: The findings point to the difficulty in maintaining ethical leadership. Key aspects to protect an organization from leadership changes are as follows: the management of the succession process, the quality of the training on ethics and the mechanisms developed by the organization to foment speak up and take notice of the situations. Moral blindness and the banality of evil that also can be observed in organizations appear as facilitating elements for collapse. Originality/value: Ethical leadership is generally presented as a necessary condition for an ethical culture. However, leaders often have unethical or ethically neutral leadership. This case helps to understand the difficulties experienced by leaders in adopting ethical leadership and proposes a set of instruments and procedures that, when included in an ethical programme, can protect the company's ethical culture against unethical leaders. Some characteristics of our case study make it particularly relevant: action occurs in a multinational, a context where, by size and complexity, achieving uniformity in culture becomes particularly relevant, and actions happen in the context of a CEO succession process, something that may occur in any company and which is often a trigger for ethical misconducts. Additionally, our case is narrated by a CEO and a CCO, which makes it rare, as it is especially difficult to have access to these executives.